ASPEK HUKUM KONSERVASI SUMBER DAYA ALAM HAYATI MELALUI PENGEMBANGAN EKOWISATA (ECOTOURISM) (STUDI DI DESA WISATA KETINGAN, DESA TIRTOADI, MLATI, SLEMAN, DIY) (THE LAW ASPECT OF THE CONSERVATION OF THE LIVE RESOURCES THROUGH THE DEVELOPMENT OF ECOTOURISM: - Handojo, Budi (Jurnal Ilmu-Ilmu Pertanian, 2008)
This research is a juridical-empirical law research equipped with data collecting instruments in the form of literary study in field study. The data itself was gained in the research area, Ketingan Tourism Village, supported with competent respondents both from government and private institutions. The data analysis is carried out with the qualitative analysis and is explained in the form of analytical description. The research result showed that both Yogyakarta KSDA Office and regional government of Sleman, in fact, do not have total policy in accordance with their right to manage the conservation of the live natural resource and the development of ecotourism in Ketingan Tourism Village. They just monitor and act out as the motivator and facilitator principle of environment oriented sustainable tourism development. The peoples activity in performing the conservation of the live natural resources through the development of ecotourism have not fully been through the same path as the environment oriented development. The problems which no way out yet like the problems of the dirt and smell of birds, fund and also room setting make the activity not maximum. Meanwhile, the participation in Ketingan Tourism Village, so far, is very positive. The will of the people and the involvement of various sides including academic circles are useful indeed and give contribution for the progress and the development of ecotourism.